A Filled‐Honeycomb‐Structured Crystal Formed by Self‐Assembly of a Janus Polyoxometalate–Silsesquioxane (POM–POSS) Co‐Cluster. Issue 52 (13th November 2015) - Ma, Chi; Wu, Han; Huang, Zi‐Han; Guo, Ruo‐Hai; Hu, Min‐Biao; Kübel, Christian; Yan, Li‐Tang; Wang, Wei
Abstract: Clusters with diverse structures and functions have been used to create novel cluster‐assembled materials (CAMs). Understanding their self‐assembly process is a prerequisite to optimize their structure and function. Herein, two kinds of unlike organo‐functionalized inorganic clusters are covalently linked by a short organic tether to form a dumbbell‐shaped Janus co‐cluster. In a mixed solvent of acetonitrile and water, it self‐assembles into a crystal with a honeycomb superstructure constructed by hexagonal close‐packed cylinders of the smaller cluster and an orderly arranged framework of the larger cluster. Reconstruction of these structural features via coarse‐grained molecular simulations demonstrates that the cluster crystallization and the nanoscale phase separation between the two incompatible clusters synergistically result in the unique nano‐architecture. Overall, this work opens up new opportunities for generating novel CAMs for advanced future applications. Abstract : How to pack dumbbells : The size asymmetry and Janus characteristics of a dumbbell‐shaped co‐cluster synergistically define its self‐assembly in solution into crystals with a filled‐honeycomb superstructure. The Janus co‐cluster consists of a POM (purple sphere) and a POSS (green sphere) linked by an organic tether.